2023
DOI: 10.1002/ejsp.3003
|View full text |Cite
|
Sign up to set email alerts
|

Examining change in social dominance and authoritarianism during New Zealand's nationwide COVID‐19 lockdown

Elena Zubielevitch,
Chris G. Sibley,
Danny Osborne

Abstract: We investigated mean‐level changes in social dominance orientation (SDO) and right‐wing authoritarianism (RWA) during (vs before) New Zealand's nationwide coronavirus disease 2019 (COVID‐19) lockdown at a time when New Zealand was led by a left‐leaning government. The number of participants in the study ranged from (Ns = 24,065–24,653). Using propensity score matching to approximate experimental conditions, results show that both ideological motivations decreased slightly during the lockdown but rebounded afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 95 publications
0
0
0
Order By: Relevance
“…It is not possible to say that any experience will not be associated with worldviews and ideologies based on our results though. For instance, it has already been shown that events such as the 9/11 attacks on the World Trade Center (Bonanno and Jost, 2006), terrorist attacks against railways in Madrid (Echebarria-Echabe and Fernández-Guede, 2006), the emergence of the COVID-19 pandemic (Azevedo et al, 2023;Zubielevitch et al, 2023), and even national elections changing the political party in power (Liu et al, 2008;Vilanova et al, 2019) significantly change worldviews and ideologies. These events have in common the fact that they are collective, contrary to the experiences we assessed, which are individual.…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible to say that any experience will not be associated with worldviews and ideologies based on our results though. For instance, it has already been shown that events such as the 9/11 attacks on the World Trade Center (Bonanno and Jost, 2006), terrorist attacks against railways in Madrid (Echebarria-Echabe and Fernández-Guede, 2006), the emergence of the COVID-19 pandemic (Azevedo et al, 2023;Zubielevitch et al, 2023), and even national elections changing the political party in power (Liu et al, 2008;Vilanova et al, 2019) significantly change worldviews and ideologies. These events have in common the fact that they are collective, contrary to the experiences we assessed, which are individual.…”
Section: Discussionmentioning
confidence: 99%